La production de terres cuites architecturales en Gaule et dans l’Occident romain, à la lumière de l’exemple de la Lyonnaise et des cités du nord-est de l’Aquitaine : un artisanat rural de caractère domanial ? - Alain Ferdière (Revue Archéologique du Centre de la France)
The question asked is about the local character of architectural terra-cotta (tiles, bricks...) in the Roman period : from the examination of the question on a Roman ‘world’ scale, at least the western parts and particularly of Gaul, the author produces an inventory of workshops for the province of Lyon and the cities North-west of the province of Aquitaine. The economic and social consequences are examined.